High resolution time series reveals cohesive but short-lived communities in coastal plankton - Antonio M. Martin-Platero (Nature Portfolio, 2018)
Whether marine microbes form strongly differentiated communities over time remains unknown. Here, Martin-Platero and colleagues develop a time series analysis to characterize marine bacteria and Eukarya communities at a fine temporal grain, revealing cohesive but rapidly changing communities.